How Do ESG Disclosure Practices Impact Firm Valuation and Capital Costs Across Different Industries? an Empirical Study - Kudakwashe Munyepwa; Liberty Mudzengerere; Pauline Machaka Charity Ranganai; Norah Chishamiso Gwesu (Goodwood Publishing, 2026)
Purpose: This study examines the impact of environmental, social, and governance (ESG) disclosure practices on firm valuation and cost of capital, focusing on how the depth, quality, and consistency of reporting influence financial outcomes. Research Methodology: The study employs a 10-year panel dataset of publicly listed firms across industries and regions, using multivariate regression and fixed-effects models. It controls for firm size, leverage, profitability, risk exposure, and industry dynamics to isolate the effect of ESG disclosure on financial performance. Results: Firms with stronger and more consistent ESG disclosures tend to achieve higher market valuations and lower costs of capital. The impact varies by sector: environmental disclosures are more influential in capital-intensive industries, while social and governance disclosures play a greater role in service-oriented sectors. Conclusions: ESG disclosure serves as a signaling mechanism and reflects effective risk management, enhancing investor confidence and supporting long-term value creation. Limitations: The study relies on secondary ESG score databases, faces potential measurement inconsistencies across regions, and excludes privately held firms. Contributions: This study provides industry-specific evidence on the financial relevance of ESG transparency, supports the need for standardized reporting frameworks, and offers insights for aligning sustainability communication with capital market expectations.